2017
DOI: 10.18632/oncotarget.17651
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pre-pregnancy body mass index and excessive gestational weight gain on the risk of gestational diabetes in advanced maternal age

Abstract: Background and purposeWith the popularization of a two-child policy in China, the number of pregnant women of advanced maternal age will increase steadily. We aimed to assess the association between pre-pregnancy body mass index (BMI) and weight gain in the first and second trimester and the risk of gestational diabetes (GDM) in the advanced maternal age group and control group defined as maternal age of 20–35 years.ResultsThe risk of GDM for obesity before pregnancy was 2.707 (95% CI: 1.042–7.029) folds and 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
19
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 24 publications
(34 reference statements)
6
19
2
Order By: Relevance
“…We did not have any information on family history of diabetes, which is one well‐known risk factor for GDM. We were also missing data on gestational weight gain; excessive weight gain is known to associated with GDM . Data on lifestyle factors such as physical activity, diet and sleeping patterns were also missing.…”
Section: Discussionmentioning
confidence: 99%
“…We did not have any information on family history of diabetes, which is one well‐known risk factor for GDM. We were also missing data on gestational weight gain; excessive weight gain is known to associated with GDM . Data on lifestyle factors such as physical activity, diet and sleeping patterns were also missing.…”
Section: Discussionmentioning
confidence: 99%
“…Association of pre-pregnancy weight and pregnancy outcomes for women with AMA. Age is a risk factor for pre-pregnancy overweight (2), and overweight can trigger GDM, HDCP, macrosomia and other adverse pregnancy outcomes (911). In this study, we demonstrated that women of AMA and overweight were more likely to develop GDM than women with normal pre-pregnancy BMIs.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we demonstrated that women of AMA and overweight were more likely to develop GDM than women with normal pre-pregnancy BMIs. A previous study demonstrated that the risk of developing GDM among women who were overweight before pregnancy was greater than the risk among pregnant women with normal pre-pregnancy weights (2). The body's glucose tolerance becomes impaired with age due to gradual islet β-cell dysfunction (12), and being overweight is associated with insulin resistance, insulin secretion abnormalities, and insulin receptor abnormalities(1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gestational diabetes and hypertensive diseases induced by pregnancy, which are observed frequently in maternal obesity, bring up the risks such as operative birth and anesthesia complications. An increase in the preterm birth rates, macrosomia, shoulder dystocia, and intrauterine, neonatal, or infant mortality are more frequent in obese mothers compared to mothers that have a normal body mass index (BMI) (3)(4)(5)(6)(7). In the literature, it was declared that maternal obesity was associated with fetal macrosomia, preterm birth, a low birth weight, neonatal hyperinsulinemia, and an increased need for neonatal intensive care (8,9).…”
Section: Introductionmentioning
confidence: 99%